Trends in pediatric central nervous system cancers in Turkey (Annals of Medical Research, 2021)
Aim: Paediatric central nervous system (CNS) cancers have a high incidence and mortality relative to other paediatric malignancies. The objective was to provide a brief, nonspecialist review of the incidence and outlook of paediatric CNS cancers in Turkey.Materials and Methods: It is based on Turkish National Cancer Statistics and data from the International Incidence of Childhood Cancer (IICC) collaborative project. The pediatric CNS cancers data of Turskish children were analyzed and compared with the World statistics data.Results: CNS cancers are the second most prevalent cancers in boys and girls in Turkey. About 21.7% of the cancers in boys and 25.5% in girls in Turkey from 2010 to 2015 were CNS tumours, which is consistent with the rates in other world regions. The Turkish National Cancer Centre reported that the ASRs/100 000 person years of pediatric CNS cancers were varying from 5 to 8.5 in boys and from 4.4 to 7.9 in girls between the years of 2010 and 2015. The group with the highest incidence of CNS cancers in childhood is observed as 0-4 years.Conclusion: Cancer registries in Turkey and international agencies such as the IICC provide reliable incidence data, but surveillance data specific to paediatric CNS tumours may not always be easy to obtain.Dedicated paediatric cancer registries worldwide and broad surveillance worldwide will increase our understanding of epidemiology these tumours.